2018
DOI: 10.18295/squmj.2018.18.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Daytime Sleepiness Among Young Adult Omani Car Drivers

Abstract: Sleepiness while driving was common among young male drivers in Oman and might be due to nocturnal sleep deprivation. Further studies are needed so that preventative measures can be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 26 publications
(32 reference statements)
3
21
0
Order By: Relevance
“…It can be performed as a day care procedure with minimal morbidity [9]. It can be performed in any age group and is especially useful in elderly patients who have other associated co-morbidities [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be performed as a day care procedure with minimal morbidity [9]. It can be performed in any age group and is especially useful in elderly patients who have other associated co-morbidities [10].…”
Section: Introductionmentioning
confidence: 99%
“…Sialendoscopy has few limitatations which include a long learning curve, difficulty in navigating small and delicate ducts with variable branching, need of a trained operator in difficult cases [10].…”
Section: Introductionmentioning
confidence: 99%
“…11,20 In this issue of SQUMJ, Al-Abri et al present novel and important findings regarding the prevalence of daytime sleepiness while driving and OSA in Muscat, Oman. 21 The authors observed that sleepiness while driving was common among Omani private motor vehicle drivers, with just over one-quarter of the drivers experiencing sleepiness while driving at least once per month. Unhealthy sleep habits appeared to be the major culprit, as almost two-thirds of the population sampled reported sleeping less than six hours per night, with evidence of a significant association between an inadequate night's sleep and feeling sleepy while driving.…”
mentioning
confidence: 99%
“…Unhealthy sleep habits appeared to be the major culprit, as almost two-thirds of the population sampled reported sleeping less than six hours per night, with evidence of a significant association between an inadequate night's sleep and feeling sleepy while driving. 21 Another alarming finding was the high rate of excessive daytime sleepiness, with 37.8% of the participants scoring greater than 10 on the ESS. The paper also reported an OSA prevalence of 10.6%, with a significant association between OSA and sleepiness while driving.…”
mentioning
confidence: 99%
See 1 more Smart Citation